Exploring Women's Experiences of Health and Well-Being in Remote Northwest Queensland, Australia. (May 2014) - Harvey, Desley
Rural and remote environments are challenging places in which to achieve health and well-being. In this woman-centered, grounded theory study, I explored the meaning of health and well-being as well as how it is achieved from the perspective of women living in remote inland parts of Australia. The study was based on semistructured interviews with 23 women living in geographically remote areas. The findings are presented as a model of the capacity to flourish. Flourishing describes an optimal achievable state of well-being, delineated by four interrelated dimensions of experience: control, connecting, belonging, and identity. I identify individual, contextual, and structural factors that enable and constrain the capacity to flourish. The findings suggest that approaches to understanding and promoting women's health in remote areas should be more holistic and contextual.